1994
DOI: 10.2337/diacare.17.5.382
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Fiber Composition and Capillary Density in Women and Men With NIDDM

Abstract: Recent information suggests that insulin may regulate myosin synthesis in muscle in the direction of the changes observed. Therefore, it is possible that muscle fiber composition abnormalities in insulin-resistant conditions are secondary to hyperinsulinemia. However, the low capillary density, hypothetically, may contribute to insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
246
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(275 citation statements)
references
References 0 publications
26
246
3
Order By: Relevance
“…Using QRT-PCR and Western blot techniques, we were able to detect a decrease in type 1 MHC mRNA and protein expression levels in PLN muscles of swine on DMetS diet. Previous studies in humans showed that obese individuals with or without NIDDM had a significantly lower percentage of type 1 and higher percentage of type 2b/x muscle fibers than lean individuals (10,17,24,25,29,35). Overall, the trends we noted in changes of fiber type composition in muscles of Ossabaw swine on MetS and DMetS diets are highly consistent with findings in obese and NIDDM humans.…”
Section: E853supporting
confidence: 89%
See 1 more Smart Citation
“…Using QRT-PCR and Western blot techniques, we were able to detect a decrease in type 1 MHC mRNA and protein expression levels in PLN muscles of swine on DMetS diet. Previous studies in humans showed that obese individuals with or without NIDDM had a significantly lower percentage of type 1 and higher percentage of type 2b/x muscle fibers than lean individuals (10,17,24,25,29,35). Overall, the trends we noted in changes of fiber type composition in muscles of Ossabaw swine on MetS and DMetS diets are highly consistent with findings in obese and NIDDM humans.…”
Section: E853supporting
confidence: 89%
“…Lillioja et al (22) showed that in vivo insulin action determined by the euglycemic clamp was positively correlated with the percentage of type 1 fibers and negatively correlated with the percentage of type 2b/x fibers in vastus lateralis muscles of humans. Several studies showed that obese individuals with or without type 2 diabetes had a significantly lower percentage of type 1 and a higher percentage of type 2b/x muscle fibers than lean individuals (2,10,17,24,25,29,35).…”
mentioning
confidence: 99%
“…Thus, it is tempting to speculate that the KE muscles of our patients could have been 5 characterized by a higher proportion of type II fibers with respect to the arm muscles 6 in reason of a greater diabetes-induced impairment as suggested by some (Gaster et 7 al., 2001;Hickey et al, 1995;Mårin et al, 1994;Mogensen et al, 2007;Oberbach et 8 al., 2006;Segerström et al, 2011;Stuart et al, 2013) but not all (Andreassen et al, 9 2014;Cederholm et al, 2000;He et al, 2001;Leenders et al, 2013;Zierath et al, 10 1996) studies. This would be reflected by lower TTF due to the greater fatigability of 11 glycolytic fibers, by the higher MFCV slopes during the fatiguing contractions, as 12 well as by the greater training effect on the torque-velocity relationship.…”
Section: Muscle Fatigue 10mentioning
confidence: 99%
“…Type 2 diabetes is also associated with an increased proportion of fast, glycolytic type 2 fibers (Marin, et al, 1994, Oberbach, et al, 2006. The transition from fast to slow fiber is more difficult to achieve in humans than the other way round.…”
Section: Strategies To Improve the Human Myotube Modelmentioning
confidence: 99%